Pengaruh Produk, Harga, Lokasi Dan Promosi Terhadap Daya Saing (Warung Soto Ayam Lamongan Cak Mardi Samarinda) - Lutfiah Rahmawaty; Budi Wahono; Etty Saraswati (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study was used to determine the effect of product, price, location, and promotion on the competitiveness of Soto Ayam Lamongan Cak Mardi Samarinda. The variables used in this study are the Competitiveness variable (dependent variable), while the independent variables are Product, Price, Location, and Promotion. The location of this research was carried out on Soto Ayam Lamongan customers who became consumers. This research was quantitative. This research used a case study method where data is obtained by distributing questionnaires to Soto Ayam Lamongan customers who are selected by purposive sampling. The determination of the number of samples used the Slovin formula and the results obtained were 99 respondents. The results of this study concluded that the Product, Price, Location, and Promotion Variables had a partial effect on the Competitiveness of Warung Soto Ayam Lamongan Cak Mardi. Keywords: Competitiveness, Product, Price, Location, Promotion